Uji Coba Elektroda Pelat Tembaga dan Alumunium Terhadap Air Laut Sebagai Elektrolit Untuk Menghasilkan Energi Listrik Alternatif - Muhammad Halil (MAJALAH TEKNIK SIMES, 2019)
The need for energy continues to increase in line with increasing development, especially in the industrial sector, economic growth and population growth. Petroleum has become the main energy source in meeting domestic energy needs. At present, petroleum is also a commodity producing state revenues and foreign exchange. The growing demand for petroleum continues, but reserves are running low. The diminishing world oil reserves, including Indonesia, has encouraged the government to reduce people's dependence on fuel oil. Sea water is a mixture of 96.5% pure water and 3.5% other materials such as salt and dissolved gases. Basically, water sea contains high NaCl compounds and by H2O decomposed into Na+ and Cl- The voltage produced from Seacell is theoretically capable of producing Electricity voltage. Test results of seawater on the influence of copper and aluminum cross-sectional area, that the cross-sectional area of ??copper and aluminum plates is very influential on the amount of electrical energy produced. Where is the cross-sectional area of ??copper and aluminum 100 cm2 = 0.00672 Watts, 150 cm2 = 0.0126 Watts, and 400 cm2 = 0.0354 Watts. This shows that electrical energy can be generated through copper plate and aluminum electrodes and sea flow as a electrolyte